HUBUNGAN KONSEP DIRI DENGAN PENERIMAAN DIRI DAN KEMANDIRIAN PADA LANSIA : LITERATUR REVIEW - Dya Sustrami (Jurnal Keperawatan Malang, 2021)
Background : Elderly is someone who is entering the age above 60 years. Elderly can be characterized by physical changes including thin and gray hair, toothless teeth, decreased hearing, decreased vision and wrinkled or sagging skin. This study aims to determine the relationship between self-concept and self-acceptance and independence in the elderly. Method : This research design is a study using the literature method or literature review. The study population was the elderly aged over 60 years. Search for journal articles using the keywords English and Indonesian as well as in combination with the boolean operator (AND, OR NOT or AND NOT). A total of 100 journals were obtained, then classification according to the inclusion criteria were 11 journals. Results : The findings that have been analyzed by researchers as a whole are formulated that "There is a relationship between self-concept and self-acceptance" and "There is no relationship between self-concept and the independence of the elderly". In addition, those that affect self-concept, self-acceptance and independence of the elderly, namely responses, social support, family support, have a significant relationship.Conclusion : Self-concept and positive and negative self-acceptance from the family, there is depression, there is no social support and support. Elderly who experience dependence caused by damage and debilitating damage, this is proven by research that has been reviewed by researchers that there is a very significant relationship.